2004
DOI: 10.1182/blood-2003-06-2073
|View full text |Cite
|
Sign up to set email alerts
|

Chronic graft-versus-host disease is associated with increased numbers of peripheral blood CD4+CD25high regulatory T cells

Abstract: Chronic graft-versus-host disease (cGVHD) is characterized by a state of profound immunodeficiency in association with alloreactive and autoimmune phenomena. These observations indicate an impairment of immunologic tolerance that could involve both central and peripheral mechanisms. Defective thymic function may contribute to dysregulation of central tolerance, but few studies have addressed peripheral tolerance. Recently a population of CD4 ؉ CD25 ؉ T cells (T reg cells) has been characterized, which controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(131 citation statements)
references
References 41 publications
(52 reference statements)
12
117
0
2
Order By: Relevance
“…To check the expansion of self-directed effector cells, it appears important that the immune system could maintain, or if necessary, amplify the level of the Treg subpopulation. Over the course of a graftvs-host reaction, for example, patients appear capable of amplifying their Treg subpopulation in an appropriate manner (59). In the case of SLE, in contrast, the homeostatic control mechanisms of the Treg population appear to be profoundly perturbed.…”
Section: Discussionmentioning
confidence: 99%
“…To check the expansion of self-directed effector cells, it appears important that the immune system could maintain, or if necessary, amplify the level of the Treg subpopulation. Over the course of a graftvs-host reaction, for example, patients appear capable of amplifying their Treg subpopulation in an appropriate manner (59). In the case of SLE, in contrast, the homeostatic control mechanisms of the Treg population appear to be profoundly perturbed.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is well known that Treg cells can prevent both aGVHD (Hoffman et al, 2002;Taylor et al, 2002;Edinger et al, 2003) and cGVHD (Zheng et al, 2004;Kim et al, 2005), little is known regarding their involvement in the pathogenesis of cGVHD versus aGVHD. In human cGVHD, there is evidence showing that Treg cells are positively associated with cGVHD (Clark et al, 2004), although contradictory data have been reported more recently (Miura et al, 2004). There is also circumstantial evidence that Treg cells are involved in the conversion of aGVHD to cGVHD; aGVHD has been shown to progress into cGVHD by rapamycin (Blazar et al, 1999) which is highly effective in inducing the proliferation of Treg cells in vitro (Battaglia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…9 These data were not confirmed by another report, which showed an increase in Tregs in subjects with cGVHD. 10 In conclusion, synovitis as a manifestation of cGVHD is a rare, but clinically relevant, condition. Accurate and early diagnosis is required for timely and appropriate treatment of the disease.…”
mentioning
confidence: 90%